Influence of anthropogenic activities and risk assessment on protected mangrove forest using traditional and emerging molecular markers (Ceará coast, northeastern Brazil) - Santos, Felipe R.; Martins, Davi A.; Morais, Pollyana C.V.; Oliveira, André H.B.; Gama, Allyne F.; Nascimento, Ronaldo F.; Choi-Lima, Katherine F. [UNESP]; Moreira, Lucas Buruaem [UNESP]; Abessa, Denis M.S. [UNESP]; Nelson, Robert K.; Reddy, Christopher M.; Swarthout, Robert F.; et al. (Elsevier, 2019)
Anthropogenic molecular markers were used to assess chemicals inputs and ecological risks associated from multiple sources to sediments in one of the largest tropical mangrove forests of South America, with a particular focus on lesser studied compounds resulting from rural activities. Total concentrations ranged from 23.4 to 228.2 ng g−1 for polycyclic aromatic hydrocarbons (∑PAHs), 750.4 to 5912.5 ng g−1 for aliphatic hydrocarbons (∑AHs), 32.4 to 696.6 ng g−1 for pesticides (∑pesticides), 23.1 to 2109.7 ng g−1 for coprostanol and sterols (∑sterols), 139.3 to 580.2 ng g−1 for naturals hormones (∑natural hormones) and 334.1 to 823.4 ng g−1 for synthetics hormones (∑synthetic hormones). The PAHs and AHs used as traditional anthropogenic markers showed a mixture between natural and anthropogenic sources, related mainly to inputs from higher plants, phytoplankton and both, biomass and petroleum combustion. Rural activities linked to agricultural pest control are the predominant source of pesticides, although minor inputs from pesticides used in urban public health campaigns and household activities were also detected. Synthetic hormones levels are two to three orders of magnitude greater than natural hormones levels and no correlations were observed between the main sewage markers and synthetic hormone concentrations, rural activities such as animal husbandry, which use drugs in management, may be the predominant anthropogenic sources of these compounds in the region. Traditional markers failed to detect ecological risks in rural areas, where synthetic substances (e.g. pesticides and hormones) are widely used and introduced in the environment.
Keywords: Emerging organic contaminants; Endocrine disrupting chemicals; Environmental fate; Estrogens; Source apportionment; Toxicity